PENGARUH TINGKAT INTENSITAS GELOMBANG ULTRASONIK TERHADAP JUMLAH SEL DARAH PUTIH (LEUKOSIT) DAN SEL DARAH MERAH (ERITROSIT) PADA MENCIT - Amrul Hadi, M. Zully; Sutapa, I Gusti Ngurah; Anta Kasmawan, I Gde (BULETIN FISIKA; Vol 17 No 1 (2016): BULETIN FISIKA, 2016)
The level of sensitivity and auditory responses observed due to the influence of sound waves can be used as bio-indicators of noise. The aims of this study are to determine the effect of the intensity level of ultrasonic waves to leukocytes and erythrocytes, and to observe the optimal intensity level that can affect the quantity of leukocytes and erythrocytes of mice. Ultrasonic waves with varying levels of intensity of 70 dB, 75 dB, 80 dB, 85 dB, and 90 dB were exposed to the mice for 2 hours, then the quantity of leukocytes and erythrocytes of the mice were observed. The average number of leukocytes in those variation of the intensity level respectively are (4,13±0,50) x10 3 ; (5,20±0,62) x10 3 ; (5,48±0,72) x10 3 ; (5,87±0,65) x10 3 dan (6,04±0,32) x10 3 ; while the average number of erythrocytes respectively are (7,29±0,14) x10 6 ; (7,10±0,22) x10 6 ; (6,18±0,24) x10 6 ;( 5,96±0,52) x10 6 ; dan (5,75±0,41) x10 6 . The average number of leukocytes increased, while erythrocytes decreased as the increasing of intensity level of ultrasonic waves. The optimal intensity level of ultrasonic waves affecting the quantity of leukocytes and erythrocytes of mice has not been known yet from this study.